Middle ear problems in children with cleft palate: A cross-sectional study - Frederick Dochy; Eva Vanheule; Els De Leenheer; Helen Van Hoecke (Archives of Otolaryngology and Rhinology - Peertechz Publications, 2019)
Background: Cleft lip and/or palate is the most common congenital craniofacial anomaly. Otitis media with effusion is almost universally present in young children with a cleft palate. OME results in a conductive hearing loss and -if persistent- often requires the placement of ventilation tubes or adjustment of hearing aids in selected cases. Also, a higher incidence of middle ear sequelae e.g. tympanic membrane perforation, chronic otitis media with or without cholesteatoma is reported in the cleft palate population.